2007
DOI: 10.1128/aac.01043-06
|View full text |Cite
|
Sign up to set email alerts
|

bla VIM-2 -Harboring Integrons Isolated in India, Russia, and the United States Arise from an Ancestral Class 1 Integron Predating the Formation of the 3′ Conserved Sequence

Abstract: The metallo-β-lactamase gene bla VIM-2 was identified in a strain of Pseudomonas aeruginosa isolated in India. The integron encoding bla VIM-2 was virtually identical to those recently found in the United States and Russia. These unusual structures are likely to have arisen from an ancestral integron predating the formation of the 3′ conserved sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 16 publications
3
39
2
1
Order By: Relevance
“…This result is consistent with findings from Japan and Tunis (Hammami et al, 2010) in which the integron carrying aacA7 and bla VIM-2 at the 59 end did not possess the 39CS. In addition, similar results have been reported in P. aeruginosa isolates (strain RON-1) isolated in Paris (Poirel et al, 2006), Portugal (Quinteira & Peixe, 2006) and India (Toleman et al, 2007). However, the downstream regions of the bla VIM-2 gene of these isolates were found to be different when compared with the P. aeruginosa isolate used in our study.…”
Section: Discussionsupporting
confidence: 72%
“…This result is consistent with findings from Japan and Tunis (Hammami et al, 2010) in which the integron carrying aacA7 and bla VIM-2 at the 59 end did not possess the 39CS. In addition, similar results have been reported in P. aeruginosa isolates (strain RON-1) isolated in Paris (Poirel et al, 2006), Portugal (Quinteira & Peixe, 2006) and India (Toleman et al, 2007). However, the downstream regions of the bla VIM-2 gene of these isolates were found to be different when compared with the P. aeruginosa isolate used in our study.…”
Section: Discussionsupporting
confidence: 72%
“…A class 1 integron carrying aacA7 and bla VIM-2 was described in Romania (30), but the downstream region of the bla VIM-2 gene was different when compared with the sequences from our study. In particular, the former integron had three gene cassettes in the variable region, aacA7, bla VIM-2 , dhfrB, similar to integrons found in Russia, United States and India (31). Almost all class 1 integrons described in our study had only two cassettes (aacA7 and bla VIM-2 ).…”
Section: Discussionmentioning
confidence: 76%
“…Another study from India also reported bla VIM-2 from P. aeruginosa [22]. In a nation-wide survey conducted to characterise 301 MBL producing Pseudomonas species in 10 medical centres from India, the MBL genes were detected in 18.9% of the isolates and 5 VIM variants were reported with VIM-2 being the most common.…”
Section: Discussionmentioning
confidence: 99%